2014
DOI: 10.1007/s00737-014-0421-z
|View full text |Cite
|
Sign up to set email alerts
|

Returning to tricyclic antidepressants for depression during childbearing: clinical and dosing challenges

Abstract: Managing depression and anxiety during pregnancy and the postpartum period is challenging. Both pharmacological treatment and the lack thereof can pose threats to a fetus. SSRIs are the drugs of choice for use during pregnancy, but there is considerable evidence for the safety and efficacy of older antidepressants during pregnancy as well. This study highlights a single case of the use of the tricyclic nortriptyline during pregnancy and postpartum. The subject involved had an unexpectedly high ratio of serum l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…1B). Furthermore, NTP has a long history of use as an antidepressant without many detectable adverse effects (Menza et al, 2009;Osborne et al, 2014). Typically, NTP dosages are 25-75 mg/ day (Krymchantowski et al, 2011;Maizels and McCarberg, 2005;Yeragani et al, 2002), which correspond to plasma concentrations up to 10 μM (Yeragani et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…1B). Furthermore, NTP has a long history of use as an antidepressant without many detectable adverse effects (Menza et al, 2009;Osborne et al, 2014). Typically, NTP dosages are 25-75 mg/ day (Krymchantowski et al, 2011;Maizels and McCarberg, 2005;Yeragani et al, 2002), which correspond to plasma concentrations up to 10 μM (Yeragani et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The C/D ratios increased to 0.80 (ng/mL)/mg at 2 weeks postpartum and 1.02 (ng/mL)/mg at 4 weeks postpartum. Another case reported the C/D ratios in a 31‐year‐old woman treated with nortriptyline as 1.1 (μg/L)/mg at 11 weeks’ gestation, 1.21 (μg/L)/mg at 30 weeks’ gestation, 1.01 (μg/L)/mg at 36 weeks’ gestation, 2.45 (μg/L)/mg at 11 weeks postpartum, and 3.0 (μg/L)/mg at 33 weeks postpartum 61 …”
Section: Resultsmentioning
confidence: 99%
“…Although 24 studies included longitudinal data with maternal plasma trough concentrations during pregnancy (most in the third trimester), at delivery, and/or postpartum, there was often a large amount of missing data. [26][27][28]30,34,35,37,39,40,42,[45][46][47][48][49][51][52][53]55,56,[59][60][61]64 For example, a study of paroxetine reported data from 74 subjects total, but data were missing from 20 subjects in the first trimester, 8 in the second trimester, and 4 in the third trimester. 52 Another study of 55 subjects had 27 missing in the third trimester and 11 missing at delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetic effects of antenatal stress and depression on fetal development ("fetal programming") are increasingly understood (19)(20)(21), as are the adverse long-term effects of postpartum depression on children (22)(23)(24)(25). In addition to these risks, there is also considerable literature on the potential risks of treatments to both mother and fetus (26)(27)(28), as well as a body of literature concerning drug disposition and pharmacokinetic changes in pregnancy and postpartum that may require dosage adjustments (29)(30)(31)(32). Clinicians who specialize in the field routinely use this new scientific information to craft individualized risk analyses for pregnant women who require treatment.…”
mentioning
confidence: 99%